2017
DOI: 10.1021/acsinfecdis.7b00027
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Nitric Oxide Binding Protein and Nitric-Oxide-Responsive Signaling Pathway in Pseudomonas aeruginosa

Abstract: Nitric oxide (NO) is a radical diatomic gas molecule that, at low concentrations, plays important signaling roles in both eukaryotes and bacteria. In recent years, it has become evident that bacteria respond to low levels of NO in order to modulate their group behavior. Many bacteria respond via NO ligation to a well-established NO sensor called H-NOX (heme-nitric oxide/oxygen binding domain). Many others, such as Pseudomonas aeruginosa, lack an annotated hnoX gene in their genome yet are able to respond to lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
107
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(115 citation statements)
references
References 60 publications
7
107
0
1
Order By: Relevance
“…This rate constant is independent of CO concentration as well as dithionite at all concentrations tested (300 μ M, 3 mM, 30 mM, and 100 mM dithionite). The VcNosP NO dissociation rate constant is comparable to both the rate constant reported for the dissociation of NO from P. aeruginosa NosP (1.8 × 10 −4 s −1 ) 11 and the reported NO dissociation rate constant for sGC (3.6 × 10 −4 s −1 ; sGC is a mammalian member of the H-NOX family). 21 Interestingly, the NO dissociation rate constant for VcNosP is much slower than the NO dissociation rate constant reported for VcH-NOX (0.3 s −1 ).…”
supporting
confidence: 81%
See 3 more Smart Citations
“…This rate constant is independent of CO concentration as well as dithionite at all concentrations tested (300 μ M, 3 mM, 30 mM, and 100 mM dithionite). The VcNosP NO dissociation rate constant is comparable to both the rate constant reported for the dissociation of NO from P. aeruginosa NosP (1.8 × 10 −4 s −1 ) 11 and the reported NO dissociation rate constant for sGC (3.6 × 10 −4 s −1 ; sGC is a mammalian member of the H-NOX family). 21 Interestingly, the NO dissociation rate constant for VcNosP is much slower than the NO dissociation rate constant reported for VcH-NOX (0.3 s −1 ).…”
supporting
confidence: 81%
“…The data were fit as described previously. 11 The measured rate of 4.6 × 10 −4 is independent of CO and dithionite at all concentrations tested (300 μ M, 3 mM, 30 mM, and 100 mM dithionite). (B) Absorbance difference spectrum where the spectrum at time = 0 min is subtracted from all subsequent spectra collected over time as the Fe II −CO complex is formed.…”
Section: Figurementioning
confidence: 90%
See 2 more Smart Citations
“…NO-bound Pa NosP has been shown to regulate the activity of a co-cistronic histidine kinase that is required for NO-dependent biofilm reduction. 11 NO-bound Vc NosP has been demonstrated to regulate the autophosphorylation activity 18 of the quorum sensing kinase VpsS, 1921 and Lpg NosP modulates a co-cistronic kinase (Fischer, et al unpublished data) whose cognate response regulator has been shown to result in a hyper-biofilm phenotype when deleted. 21, 22 …”
Section: Introductionmentioning
confidence: 99%